If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + -1) = 2y + 18 Reorder the terms: 6(-1 + y) = 2y + 18 (-1 * 6 + y * 6) = 2y + 18 (-6 + 6y) = 2y + 18 Reorder the terms: -6 + 6y = 18 + 2y Solving -6 + 6y = 18 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -6 + 6y + -2y = 18 + 2y + -2y Combine like terms: 6y + -2y = 4y -6 + 4y = 18 + 2y + -2y Combine like terms: 2y + -2y = 0 -6 + 4y = 18 + 0 -6 + 4y = 18 Add '6' to each side of the equation. -6 + 6 + 4y = 18 + 6 Combine like terms: -6 + 6 = 0 0 + 4y = 18 + 6 4y = 18 + 6 Combine like terms: 18 + 6 = 24 4y = 24 Divide each side by '4'. y = 6 Simplifying y = 6
| 2*x^2+10x+2=0 | | 81y^4-72y^2+16=0 | | 8ln(7x)=16 | | -9x-208=55+2x | | 2y+8z=-32 | | -x-62=10x+92 | | 14=x-30 | | 46+m=16 | | 8x-y+3z=20 | | n+27=-60 | | -25x+2x=4x+15 | | x-38=18 | | 3X^2+12X-33=0 | | 0.375z+1=3 | | -6x-198=3x+63 | | 9a-2ab-6-9ab+4a= | | (2x^2)-6x-15=0 | | x^6-9x^5+24x^4-20x^3=0 | | 5x+5y-8x-3y= | | 7c-3c=-2c-8 | | 2x-49=95+11x | | 2t=-3(t+10) | | -11x-111=65-3x | | 3x+14y=2 | | 4x^2-21x+21=-5x+6 | | -10x-60=3x+73 | | -108+5x=124-3x | | (3-2x)=(3-x) | | 6=-5x^2+11x | | 6=-5x+11x | | 36=-x^2+12x | | 15m^2-19m+6=0 |